Da desconfiança à aliança: Portugal e a África do Sul na defesa do “Reduto Branco - Barroso, L. (Bulletin for Spanish and Portuguese Historical Studies, 2014)
This paper aims to analyze the diplomatic maneuver carried out by the Portuguese Government towards South Africa since the 1950’s until the military coup in Lisbon on the 25th April 1974. In October 1970, Portugal, South Africa and Rhodesia initiated a formal military alliance coined as “Exercise ALCORA”. Its final aim was to defeat the pan-Africanism subversion in Southern Africa but it also became a mechanism to integrate the most important aspects of the military strategy of the “white redoubt”. The participation of Portugal in ALCORA was the result of its political maneuver towards South Africa since de 1950’s although Salazar and later Caetano were concerned and feared South African political hegemony and pretensions over Angola and Mozambique. In spite of the racial policy of both countries, Portugal was granted important financial and military support by South Africa because its government recognized Mozambique and Angola as its first line defense against the communist subversion. In fact, the degradation of the military situation in southern Angola in the late 1960’s definitely pushed those territories to South Africa's strategic orbit.